1996
DOI: 10.1007/bf00304077
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and urinary calcium stone formation in northwestern India: a case control study

Abstract: The nutrient intake of 69 stone formers (SFs) from three subsets of the local population (urban 22, rural tribal 22 and rural nontribal 25) and 69 age, sex, weight and socioeconomically matched control subjects (NSs) (urban 20, rural tribal 22 and rural nontribal 27) was studied. Simultaneously their times 24-h urine samples collected over a similar period were analyzed. In general caloric and protein intake was low in all the groups but was strikingly low in the rural subjects. Intake of all nutrients was low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Increased use of spices (17) in food may be a contributory factor to increased stone formation in the urinary tract. The distribution of urolithiasis is not uniform (5) but in western India urolithiasis is present in <4.5 per 10 000 population (18) under 40 yr of age. In the present study, urolithiasis was found to be significantly higher (OR 23.4; 95% CI 18.26–28.7; λ 2 test P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased use of spices (17) in food may be a contributory factor to increased stone formation in the urinary tract. The distribution of urolithiasis is not uniform (5) but in western India urolithiasis is present in <4.5 per 10 000 population (18) under 40 yr of age. In the present study, urolithiasis was found to be significantly higher (OR 23.4; 95% CI 18.26–28.7; λ 2 test P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…However, investigations of such patients rarely demonstrate urolithiasis (1). Urolithiasis has multiple aetiologies (2–4) including certain geographical locations of endemic fluorosis (5, 6). The present study was carried out in the western Indian state of Maharashtra, which is not arid and has only a small foci of endemic fluorosis.…”
mentioning
confidence: 99%